Polyamide composition and use and connector

CN122404973BActive Publication Date: 2026-10-30SHANGHAI KINGFA SCI & TECH +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610875500.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-10-30
Estimated Expiration
2046-06-17

AI Technical Summary

Technical Problem

而且,在连接器的SMT过程中,如果不通氮气,聚酰胺树脂中的酰胺键会和空气中的氧气结合,造成材料变色,不能满足客户的美学要求,所以,也期待聚酰胺材料具有良好的耐烘烤变色性能

Benefits of technology

在无卤阻燃剂和聚酰胺(PA)树脂的体系中,不同重均分子量的间规聚苯乙烯A和间规聚苯乙烯B能够与PA树脂形成结构良好的相结构,而马来酸酐接枝聚苯醚(MAH-g-PPE)利用其自身的马来酸酐端与PA树脂反应、以及聚苯醚端与间规聚苯乙烯A和/或B互溶来提高间规聚苯乙烯A和/或B与PA树脂之间的相容性,从而提高相结构的结构稳定性,以及促进该相结构在体系中的均匀分散,有利于降低界面损耗,进而达到降低聚酰胺组合物Dk和Df、以及提高聚酰胺组合物平面度和耐烘烤变色性能的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of polyamide composition and application and connector, polyamide composition includes following weight parts of each component: 5-55 parts polyamide resin, 5-35 parts syndiotactic polystyrene complex, 5-25 parts halogen-free flame retardant, 0.5-7 parts maleic anhydride grafting polyphenyl ether;The polyamide resin is semi-aromatic polyamide;Syndiotactic polystyrene complex includes the syndiotactic polystyrene A with molecular weight of 4 million-5 million and the syndiotactic polystyrene B with molecular weight of 9 million-10 million.The polyamide composition of the application has low Dk and Df, and high flatness and strong baking discoloration resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and more specifically, to a polyamide composition and its applications and connectors. Background Technology

[0002] As AI and big data computing servers continue to expand their applications, there is a strong need to build supercomputing platforms. Currently, signal transmission rates have reached 17 Gbps, and the amount of signal transmission and computation is constantly increasing. Therefore, while maintaining the overall size of the product, more memory modules and graphics card components need to be accommodated on a single circuit board. This leads to the continuous compression of connector size, meaning connectors are becoming smaller and thinner. To ensure distortion-free signal transmission, higher requirements are placed on the dielectric constant (Dk) and dissipation factor (Df) of connector materials. Materials are expected to have both low Dk and Df to meet the structural design requirements of products with high signal transmission rates, high signal transmission volumes, and high computational demands while maintaining smaller metal terminals and spacing. Simultaneously, due to the smaller and thinner connectors, the materials are more prone to warping and deformation under the same SMT (Surface Mount Technology) temperatures, thus placing higher demands on connector flatness.

[0003] Currently, in the server industry, to meet the flame retardant and strength requirements of connectors, polyamide materials containing halogen-free flame retardants are frequently chosen for connector manufacturing. Furthermore, during the SMT process of connectors, if nitrogen is not introduced, the amide bonds in the polyamide resin will combine with oxygen in the air, causing the material to discolor and failing to meet customer aesthetic requirements. Therefore, good resistance to baking discoloration in polyamide materials is also desirable.

[0004] Therefore, it is of great significance to develop a polyamide composition with low Dk and Df, high flatness and strong resistance to baking and color change, and with the addition of halogen-free flame retardants. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a polyamide composition, its application, and a connector.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a polyamide composition comprising the following components in parts by weight: 5-55 parts polyamide (PA) resin, 5-35 parts syndiotactic polystyrene compound, 5-25 parts halogen-free flame retardant, 0.5-7 parts maleic anhydride-grafted polyphenylene ether (MAH-g-PPE); wherein the polyamide resin is a semi-aromatic polyamide. The syndiotactic polystyrene compound includes syndiotactic polystyrene A with a weight-average molecular weight (Mw) of 40,000-50,000 and syndiotactic polystyrene B with a weight-average molecular weight (Mw) of 90,000-100,000.

[0007] In the system of halogen-free flame retardants and polyamide (PA) resins, syndiotactic polystyrene A and syndiotactic polystyrene B with different weight-average molecular weights can form a well-structured phase with PA resin. Maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) utilizes its maleic anhydride end to react with PA resin and the polyphenylene ether end to be miscible with syndiotactic polystyrene A and / or B to improve the compatibility between syndiotactic polystyrene A and / or B and PA resin, thereby improving the structural stability of the phase structure and promoting the uniform dispersion of the phase structure in the system. This helps to reduce interfacial losses, thereby reducing the Dk and Df values ​​of the polyamide composition and improving the flatness and baking resistance of the polyamide composition.

[0008] Furthermore, it is worth noting that when the weight-average molecular weights of syndiotactic polystyrene A and syndiotactic polystyrene B are too high or too low, it will not only affect the phase structure formed with PA resin, but also affect the dispersion of the phase structure in the system, which is not conducive to reducing the Dk and Df of the polyamide composition, as well as improving the flatness and baking resistance of the polyamide composition.

[0009] Preferably, the weight-average molecular weight (Mw) of the syndiotactic polystyrene A is one or any two of the following: 40,000, 41,000, 42,000, 43,000, 44,000, 45,000, 46,000, 47,000, 48,000, 49,000, and 50,000.

[0010] Preferably, the weight-average molecular weight (Mw) of the syndiotactic polystyrene B is one or any two of the following: 90,000, 91,000, 92,000, 93,000, 94,000, 95,000, 96,000, 97,000, 98,000, 99,000, and 100,000.

[0011] In this invention, the test standard for the weight-average molecular weight of syndiotactic polystyrene A and / or B is GB / T 36214.4-2018. The specific test method is as follows: a high-temperature gel permeation chromatography system (GPC-IR, Polymer Char, Spain, equipped with dual infrared and viscosity detectors) is used, with 1,2,4-trichlorobenzene as the mobile phase, a flow rate of 1.0 mL / min, a column temperature of 160℃, a detector temperature of 160℃, and an injector temperature of 160℃; a calibration curve is established using polystyrene standards (weight-average molecular weight range: 266-12,900,000 g / mol); the sample (syndiotactic polystyrene A and / or B) is dissolved in trichlorobenzene (concentration 0.125 mg / mL), and the injection volume is 200 μL; the data are processed by GPC ONE software to obtain the weight-average molecular weight of syndiotactic polystyrene A and / or B.

[0012] Preferably, the weight ratio of syndiotactic polystyrene A to syndiotactic polystyrene B is 1:(2-4).

[0013] Preferably, the weight ratio of the syndiotactic polystyrene A and syndiotactic polystyrene B is one or any two of the following: 1:2, 1:2.2, 1:2.3, 1:2.5, 1:2.7, 1:2.8, 1:3, 1:3.2, 1:3.3, 1:3.5, 1:3.7, 1:3.8, and 1:4.

[0014] More preferably, the weight ratio of syndiotactic polystyrene A to syndiotactic polystyrene B is 1:(2-3).

[0015] In this invention, the syndiotactic polystyrene A and / or B with different weight-average molecular weights can be obtained commercially or prepared by methods commonly used in the art.

[0016] Preferably, the molecular weight distribution of the syndiotactic polystyrene is 1.6-2.1.

[0017] Preferably, the molecular weight distribution of the syndiotactic polystyrene is within the range of one or any two of 1.6, 1.7, 1.8, 1.9, 2.0, and 2.1.

[0018] Preferably, the maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) is 0.5-1.5%.

[0019] Preferably, the maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) is within the range of one or any two of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, and 1.5%.

[0020] More preferably, the maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) is 1.0-1.5%.

[0021] In this invention, the maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) can be obtained commercially or prepared using methods commonly used in the art. A method for preparing the maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) is provided herein, comprising the following steps: melt extrusion of maleic anhydride, polyphenylene ether, and an initiator to obtain maleic anhydride-grafted polyphenylene ether (MAH-g-PPE). In the method for preparing maleic anhydride-grafted polyphenylene ether (MAH-g-PPE), the melt extrusion temperature is 260-290°C; the initiator is at least one selected from 1,4-di-tert-butylperoxyisopropylbenzene, dicumyl peroxide, benzoyl peroxide, and di-tert-butyl peroxide.

[0022] In this invention, the maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) is tested by acid-base titration. Specifically, acetone is used as a solvent to remove unreacted maleic anhydride from MAH-g-PPE by Soxhlet extraction. Then, MAH-g-PPE is dissolved in an organic solvent (such as xylene). Then, an excess of strong base (such as sodium hydroxide) is added to hydrolyze the anhydride groups. Then, the unreacted strong base is back-titrated with a strong acid (such as hydrochloric acid). Finally, the maleic anhydride grafting rate of MAH-g-PPE is calculated based on the titration results.

[0023] Preferably, the semi-aromatic polyamide is a homopolymer of a semi-aromatic polyamide and / or a copolymer thereof.

[0024] More preferably, the semi-aromatic polyamide is derived from a diacid and a diamine, wherein the diacid includes aromatic dicarboxylic acids and optionally aliphatic diacids, and the diamine includes aliphatic diamines. Even more preferably, the aliphatic diacid and / or aromatic dicarboxylic acids and / or aliphatic diamines have 4-12 carbon atoms; the number of carbon atoms can be, for example, 4, 5, 6, 7, 8, 9, 10, 11, 12, or a range of the above values, such as 6-12 or 6-10 carbon atoms.

[0025] More preferably, the aromatic dicarboxylic acid includes at least one of terephthalic acid and isophthalic acid.

[0026] More preferably, the aromatic dicarboxylic acid accounts for 55-100% of the molar percentage of the diacid unit, for example, 55-60%.

[0027] For example, the semi-aromatic polyamide includes, but is not limited to, at least one of PA6T, PA9T, PA10T, PA12T, and PA6T / 66.

[0028] Preferably, the polyamide resin has a relative viscosity of 1.5-3.5.

[0029] Preferably, the relative viscosity of the polyamide resin is a range of one or any two of the following: 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, and 3.5.

[0030] More preferably, the polyamide resin has a relative viscosity of 1.5-3.0.

[0031] More preferably, the relative viscosity of the polyamide resin is 1.5-2.5, specifically 1.8-2.4.

[0032] In this invention, the relative viscosity of the polyamide resin was measured according to the GB / T 12006.1-2009 standard. The test conditions were a 96% sulfuric acid solution, an ambient temperature of 25°C, and a polyamide resin concentration of 0.03 g / mL.

[0033] In this invention, the polyamide resin can be obtained by purchasing commercially available products or prepared by methods commonly used in the art.

[0034] Commonly used halogen-free flame retardants in this field can be used in this invention. For example, the halogen-free flame retardants include, but are not limited to, at least one of aluminum diethylphosphonate, triphenyl phosphate (TPP), triphenyl phosphite, DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide), and ammonium polyphosphate (APP).

[0035] Preferably, the polyamide composition further includes fillers.

[0036] In this invention, fillers commonly used in the art can be used. For example, the fillers include, but are not limited to, at least one of glass fiber and carbon fiber.

[0037] More preferably, the filler is 0-55 parts by weight, specifically 10-55 parts.

[0038] More preferably, the weight parts of the filler are one or any two of the following: 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 ​​parts, 50 parts, 53 parts, and 55 parts.

[0039] More preferably, the filler is 15-50 parts by weight.

[0040] Preferably, in the polyamide composition, the polyamide (PA) resin is in the range of one or any two of the following weight parts: 5 parts, 8 parts, 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 ​​parts, 50 parts, 53 parts, and 55 parts; and the syndiotactic polystyrene compound is in the range of 5 parts, 8 parts, 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, and 30 parts. The weight range of 33 parts, 35 parts, or any two of these values; the weight range of halogen-free flame retardant is 5 parts, 8 parts, 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, or any two of these values; and the weight range of maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) is 0.5 parts, 0.8 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, or any two of these values.

[0041] Preferably, the polyamide composition comprises the following components in parts by weight: 10-50 parts polyamide (PA) resin, 10-30 parts syndiotactic polystyrene compound, 10-20 parts halogen-free flame retardant, and 1-5 parts maleic anhydride-grafted polyphenylene ether (MAH-g-PPE).

[0042] Preferably, based on the weight of the polyamide composition, the polyamide (PA) resin has a weight percentage of ≥20%, specifically 25%-40%.

[0043] In a second aspect, the present invention provides a method for preparing a polyamide composition, comprising the following steps: Mix the components, melt-extrude, and you will get a polyamide composition.

[0044] Preferably, the melt extrusion temperature is 290-320℃.

[0045] Thirdly, the present invention provides an application of a polyamide composition in a connector.

[0046] Fourthly, the present invention provides a connector comprising the above-described polyamide composition, wherein the connector includes at least one of a high-voltage connector and an energy storage connector.

[0047] Compared with the prior art, the beneficial effects of the present invention are as follows: In the system of halogen-free flame retardants and polyamide (PA) resins, syndiotactic polystyrene A and syndiotactic polystyrene B with different weight-average molecular weights can form a well-structured phase with PA resin. Maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) improves the compatibility between syndiotactic polystyrene A and / or B and PA resin by reacting its maleic anhydride end with PA resin and by the miscibility of its polyphenylene ether end with syndiotactic polystyrene A and / or B. This improves the structural stability of the phase structure and promotes the uniform dispersion of the phase structure in the system, which helps to reduce interfacial loss. In this way, it can reduce the Dk and Df of the polyamide composition and improve the flatness and baking resistance of the polyamide composition.

[0048] Furthermore, it is worth noting that when the weight-average molecular weights of syndiotactic polystyrene A and syndiotactic polystyrene B are too high or too low, it will not only affect the phase structure formed with PA resin, but also affect the dispersion of the phase structure in the system, which is not conducive to reducing the Dk and Df of the polyamide composition, as well as improving the flatness and baking resistance of the polyamide composition. Detailed Implementation

[0049] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0050] The experimental methods used in the following examples and comparative examples, unless otherwise specified, are generally performed under conventional conditions in the art or as recommended by the manufacturer. Unless otherwise specified, all raw materials and reagents used are commercially available from the general market. Furthermore, unless otherwise specified, "parts" and "%" refer to mass measurements.

[0051] The reagents used in the various embodiments and comparative examples of this invention are as follows: Polyamide resin-1 (PA-1), a semi-aromatic polyamide with a relative viscosity of 2.1, is prepared as follows: under nitrogen and a pressure of 2.8 MPa, hexamethylenediamine, adipic acid, terephthalic acid, benzoic acid (a capping agent), and deionized water are mixed, heated to 180°C for 15 hours, and then heated to 235°C for another 15 hours to obtain polyamide resin-1 (PA-1). The molar ratio of hexamethylenediamine, adipic acid, and terephthalic acid is 50:22.5:27.5; the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of benzoic acid (capping agent) is (hexamethylenediamine + adipic acid + terephthalic acid): benzoic acid = 100:5; and the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of deionized water is (hexamethylenediamine + adipic acid + terephthalic acid): deionized water = 100:25. Polyamide resin-2 (PA-2), a semi-aromatic polyamide with a relative viscosity of 1.8, is prepared as follows: under nitrogen and a pressure of 2.8 MPa, hexamethylenediamine, adipic acid, terephthalic acid, benzoic acid (a capping agent), and deionized water are mixed, heated to 180°C for 13 hours, and then heated to 235°C for another 13 hours to obtain polyamide resin-2 (PA-2). The molar ratio of hexamethylenediamine, adipic acid, and terephthalic acid is 50:22.5:27.5; the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of benzoic acid (capping agent) is (hexamethylenediamine + adipic acid + terephthalic acid): benzoic acid = 100:5; and the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of deionized water is (hexamethylenediamine + adipic acid + terephthalic acid): deionized water = 100:25. Polyamide resin-3 (PA-3), a semi-aromatic polyamide with a relative viscosity of 2.4, is prepared as follows: under nitrogen and a pressure of 2.8 MPa, hexamethylenediamine, adipic acid, terephthalic acid, benzoic acid (a capping agent), and deionized water are mixed, heated to 180°C for 21 hours, and then heated to 235°C for another 21 hours to obtain polyamide resin-3 (PA-3). The molar ratio of hexamethylenediamine, adipic acid, and terephthalic acid is 50:22.5:27.5; the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of benzoic acid (capping agent) is (hexamethylenediamine + adipic acid + terephthalic acid): benzoic acid = 100:5; and the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of deionized water is (hexamethylenediamine + adipic acid + terephthalic acid): deionized water = 100:25. Polyamide resin-4 (PA-4), a semi-aromatic polyamide with a relative viscosity of 3.0, is prepared as follows: under nitrogen and a pressure of 2.8 MPa, hexamethylenediamine, adipic acid, terephthalic acid, benzoic acid (a capping agent), and deionized water are mixed, heated to 180°C for 35 hours, and then heated to 235°C for another 35 hours to obtain polyamide resin-4 (PA-4). The molar ratio of hexamethylenediamine, adipic acid, and terephthalic acid is 50:22.5:27.5; the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of benzoic acid (capping agent) is (hexamethylenediamine + adipic acid + terephthalic acid): benzoic acid = 100:5; and the ratio of the total mass of hexamethylenediamine, adipic acid, and terephthalic acid to the mass of deionized water is (hexamethylenediamine + adipic acid + terephthalic acid): deionized water = 100:25. Polyamide resin-5 (PA-5), a semi-aromatic polyamide with a relative viscosity of 2.2, is prepared as follows: under nitrogen and a pressure of 2.8 MPa, decanediamine, terephthalic acid, benzoic acid (a capping agent), and deionized water are mixed, heated to 180°C for 1 hour, and then heated to 235°C for another 2 hours to obtain the polyamide resin. The molar ratio of decanediamine to terephthalic acid is 50:50, the ratio of the total mass of decanediamine and terephthalic acid to the mass of benzoic acid (capping agent) is (decanediamine + terephthalic acid): benzoic acid = 100:4, and the ratio of the total mass of decanediamine and terephthalic acid to the mass of deionized water is (decanediamine + terephthalic acid): deionized water = 100:1000. Polyamide resin-6 (PA-6), relative viscosity 2.2, PA66 ERP-24, Pingdingshan Shenma Engineering Plastics Co., Ltd.; Syndiotactic polystyrene A-5 (sPS-A5), with a weight-average molecular weight (Mw) of 70,000, is prepared according to CN112646066B using the following method: The dried reactor was evacuated and rinsed three times with nitrogen. At a polymerization temperature of 55°C, 3.8 L of toluene, 10.0 L of styrene, 9.0 L of methylaluminoxane toluene solution (containing 15 mol of methylaluminoxane), and 2.0 L of pentamethylcyclopentadienyl-4-quinolinoxy-dimethoxytitanium catalyst toluene solution (containing 10 mmol of catalyst) were added sequentially. Timing was started, and after 2 hours of polymerization, acidified ethanol was added and stirred thoroughly. The polymer was obtained by filtration, vacuum dried at 60°C, and weighed. The polymer was refluxed in boiling acetone for 2 hours, filtered while hot, and a solid polymer was obtained. The solid polymer was then vacuum dried at 60°C to obtain syndiotactic polystyrene A-5 (sPS-A5). Based on the above-mentioned preparation method of syndiotactic polystyrene A-5 (sPS-A5), by adjusting the amount of catalyst methylaluminoxane (MAO), and thus the MAO / Ti ratio, the following sPS with different weight-average molecular weights were obtained: Syndiotactic polystyrene A-1 (sPS-A1), weight-average molecular weight (Mw) = 45,000; Syndiotactic polystyrene A-2 (sPS-A2), weight-average molecular weight (Mw) = 40,000; Syndiotactic polystyrene A-3 (sPS-A3), weight-average molecular weight (Mw) = 50,000; Syndiotactic polystyrene A-4 (sPS-A4), weight-average molecular weight (Mw) = 20,000; Syndiotactic polystyrene B-1 (sPS-B1), weight-average molecular weight (Mw) = 95,000; Syndiotactic polystyrene B-2 (sPS-B2), weight-average molecular weight (Mw) = 90,000; Syndiotactic polystyrene B-3 (sPS-B3), weight-average molecular weight (Mw) = 100,000; Syndiotactic polystyrene B-4 (sPS-B4), weight-average molecular weight (Mw) = 120,000; Halogen-free flame retardant, aluminum diethylphosphinate, commercially available; Maleic anhydride-grafted polyphenylene ether-1 (MAH-g-PPE-1), with a maleic anhydride grafting rate of 1.3%, is prepared by melt extrusion of maleic anhydride, polyphenylene ether (LXN040, Nantong Xingchen), and initiator (1,4-di-tert-butylperoxyisopropylbenzene) at 280°C to obtain maleic anhydride-grafted polyphenylene ether (MAH-g-PPE); the mass ratio of maleic anhydride, polyphenylene ether, and initiator is 1.4:98.3:0.3. Maleic anhydride-grafted polyphenylene ether-2 (MAH-g-PPE-2), with a maleic anhydride grafting rate of 1.0%, is prepared by melt extrusion of maleic anhydride, polyphenylene ether (LXN040, Nantong Xingchen), and initiator (1,4-di-tert-butylperoxyisopropylbenzene) at 280°C to obtain maleic anhydride-grafted polyphenylene ether (MAH-g-PPE); the mass ratio of maleic anhydride, polyphenylene ether, and initiator is 1.1:98.6:0.3. Maleic anhydride-grafted polyphenylene ether-3 (MAH-g-PPE-3), with a maleic anhydride grafting rate of 1.5%, is prepared by melt extrusion of maleic anhydride, polyphenylene ether (LXN040, Nantong Xingchen), and initiator (1,4-di-tert-butylperoxyisopropylbenzene) at 280°C to obtain maleic anhydride-grafted polyphenylene ether (MAH-g-PPE); the mass ratio of maleic anhydride, polyphenylene ether, and initiator is 1.6:98.1:0.3. Maleic anhydride-grafted polyphenylene ether-4 (MAH-g-PPE-4), with a maleic anhydride grafting rate of 0.5%, is prepared by melt extrusion of maleic anhydride, polyphenylene ether (LXN040, Nantong Xingchen), and initiator (1,4-di-tert-butylperoxyisopropylbenzene) at 280°C to obtain maleic anhydride-grafted polyphenylene ether (MAH-g-PPE); the mass ratio of maleic anhydride, polyphenylene ether, and initiator is 0.6:99.1:0.3. Filler, glass fiber, ECS13-04-508A, China Jushi Co., Ltd.

[0052] In this invention, the relative viscosity of the polyamide resin was measured according to the GB / T 12006.1-2009 standard. The test conditions were a 96% sulfuric acid solution, an ambient temperature of 25°C, and a polyamide resin concentration of 0.03 g / mL.

[0053] In this invention, the test standard for the weight-average molecular weight of syndiotactic polystyrene A and / or B is GB / T 36214.4-2018. The specific test method is as follows: a high-temperature gel permeation chromatography system (GPC-IR, Polymer Char, Spain, equipped with dual infrared and viscosity detectors) is used, with 1,2,4-trichlorobenzene as the mobile phase, a flow rate of 1.0 mL / min, a column temperature of 160℃, a detector temperature of 160℃, and an injector temperature of 160℃; a calibration curve is established using polystyrene standards (weight-average molecular weight range: 266-12,900,000 g / mol); the sample (syndiotactic polystyrene A and / or B) is dissolved in trichlorobenzene (concentration 0.125 mg / mL), and the injection volume is 200 μL; the data are processed by GPC ONE software to obtain the weight-average molecular weight of syndiotactic polystyrene A and / or B.

[0054] In this invention, the maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether (MAH-g-PPE) is tested using an acid-base titration method, specifically as follows: Take 5g of MAH-g-PPE and remove unreacted maleic anhydride from MAH-g-PPE by Soxhlet extraction for 24h using acetone as solvent. Then, dissolve MAH-g-PPE in 100mL of xylene, an organic solvent at 120℃. Add excess strong base (20mL of 0.1mol / L sodium hydroxide solution) to hydrolyze the anhydride groups. Then, back titrate the unreacted strong base with 0.1mol / L hydrochloric acid. Finally, calculate the maleic anhydride grafting rate of MAH-g-PPE based on the titration results.

[0055] Examples 1-17 and Comparative Examples 1-7 Examples 1-17 and Comparative Examples 1-7 provide different polyamide compositions, which differ from each other only in the type and amount of each component. By weight, Examples 1-17 and Comparative Examples 1-7 include the components shown in Table 1-2. The preparation methods of the polyamide compositions of Examples 1-17 and Comparative Examples 1-7 include the following steps: The components are mixed and melt-extruded at 300°C using a twin-screw extruder (length-to-diameter ratio 52:1, speed 200 rpm), and then granulated to obtain a polyamide composition. Table 1. Parts by weight of each component in the polyamide compositions of Examples 1-8 Table 2. Parts by weight of each component in the polyamide compositions of Examples 9-17 Table 3 shows the weight parts of each component in the polyamide compositions of Comparative Examples 1-7. Performance testing The performance of the polyamide compositions in each example and comparative example was tested, as detailed below: 1. Dielectric constant (Dk) and dissipation factor (Df) test The polyamide composition was heated and melted at 310°C and injection molded to produce a flat test piece of 100mm×100mm×2mm. The dielectric constant (Dk) and dissipation factor (Df) at a frequency of 2.5GHz were then determined according to the ASTM D2520 standard using the Split Dielectric Resonator Method (SPDR method). 2. Flatness test The polyamide composition was heated and melted at 310℃ and injection molded to produce a flat test piece of 100mm×100mm×2mm. The height of the lower right corner of the test piece was measured and recorded as H1 (in mm). Then, the test piece was baked at a speed of 480mm / min through a high-temperature testing furnace (divided into four different temperature zones: 240℃, 260℃, 280℃, and 300℃) for 7 minutes and 30 seconds. Next, a 1kg weight was placed on the upper left corner of the test piece, and the height of the lower right corner was measured (in mm), H2 (in mm). The flatness H (in mm) of the polyamide composition was calculated using the following formula: H (unit: mm) = H2 - H1; The smaller the value of H, the better the flatness of the polyamide composition; 3. Baking resistance and color change test The polyamide composition was heated and melted at 310℃ and injection molded to form a 60mm×60mm×1mm square plate. The square plate sample was baked at a speed of 480mm / min through a high-temperature test furnace (divided into 4 different temperature zones, namely 240℃, 260℃, 280℃ and 300℃ respectively) for 7 minutes and 30 seconds. The LAB value of the square plate sample before and after baking was measured, and the color difference ΔE of the square plate sample before and after baking was calculated. The smaller ΔE is, the closer the LAB values ​​of the square plate sample are before and after baking, which means that the polyamide composition has stronger resistance to baking discoloration. The experimental results are shown in the table below: Table 4 Performance test results of the polyamide compositions of each example and comparative example. In the table above, the " / " in Comparative Example 7 indicates that the polyamide composition of Comparative Example 7 melted, making it impossible to measure the corresponding flatness H and color difference ΔE.

[0056] As shown in Table 4, the polyamide composition of the present invention has low Dk and Df, as well as high flatness and strong resistance to baking discoloration, wherein Dk≤3.75, Df≤0.92, flatness H≤0.70, and ΔE≤4.5.

[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A polyamide composition, characterized in that, The components include the following parts by weight: 30-55 parts polyamide resin, 5-30 parts syndiotactic polystyrene compound, 5-25 parts halogen-free flame retardant, 0.5-7 parts maleic anhydride-grafted polyphenylene ether; wherein the polyamide resin is a semi-aromatic polyamide. The syndiotactic polystyrene compound includes syndiotactic polystyrene A with a weight average molecular weight of 40,000-50,000 and syndiotactic polystyrene B with a weight average molecular weight of 90,000-100,000. The weight ratio of syndiotactic polystyrene A to syndiotactic polystyrene B is 1:(2-4).

2. The polyamide composition according to claim 1, characterized in that, The maleic anhydride grafting rate of the maleic anhydride-grafted polyphenylene ether is 1.0-1.5%.

3. The polyamide composition according to claim 1, characterized in that, The relative viscosity of the polyamide resin is 1.5-3.

5.

4. The polyamide composition according to claim 1, characterized in that, Includes at least one of the following (1)-(3): (1) The halogen-free flame retardant includes at least one of aluminum diethylphosphonate, triphenyl phosphate, triphenyl phosphite, DOPO, and ammonium polyphosphate; (2) The polyamide composition further includes fillers, wherein the fillers include at least one of glass fiber and carbon fiber; (3) The semi-aromatic polyamide is a homopolymer of semi-aromatic polyamide and / or a copolymer thereof.

5. The polyamide composition according to claim 1, characterized in that, The semi-aromatic polyamide is derived from a diacid and a diamine, wherein the diacid includes aromatic dicarboxylic acids and optionally aliphatic diacids, and the diamine includes aliphatic diamines.

6. The polyamide composition according to claim 5, characterized in that, Includes at least one of the following (1)-(3): (1) The aliphatic diacid and / or aromatic dicarboxylic acid and / or aliphatic diamine have 4-12 carbon atoms; (2) The aromatic dicarboxylic acid includes at least one of terephthalic acid and isophthalic acid; (3) The aromatic dicarboxylic acid accounts for 55-100% of the molar percentage of the dicarboxylic acid unit.

7. The polyamide composition according to claim 1, characterized in that, The polyamide composition comprises the following components in parts by weight: 30-50 parts polyamide resin, 10-30 parts syndiotactic polystyrene compound, 10-20 parts halogen-free flame retardant, and 1-5 parts maleic anhydride-grafted polyphenylene ether.

8. The use of a polyamide composition as described in any one of claims 1-7 in a connector.

9. A connector, characterized in that, The connector comprises a polyamide composition as described in any one of claims 1-7, and includes at least one of a high-voltage connector and an energy storage connector.

Citation Information

Patent Citations

  • A catalytic polymerization system and polymerization method for styrene polymerization and the resulting polystyrene

    CN112646066B

  • A polystyrene / polyamide blended alloy material and a preparing method thereof

    CN104693630A

  • Heat-resistant flame-retardant reinforced polyamide composition as well as preparation method and application thereof

    CN119242035A